Sociabilidades e esporte: a mulher belenense em “a semana: revista illustrada” (Belém do Pará, década de 1920) - ROCHA, Andrei das Chagas (2022)
Delimiting the 1920s as the time frame, the research analyzed the profile of woman constructed by the periodical “A Semana: Revista Illustrada”. The research problem was expressed as follows: “What is the profile of a woman present in ‘A Semana: Revista Illustrada’ throughout the 1920s?” The objective was to understand the profile of woman constructed by this journal. The research was constituted as historiographical, of documentary character, using Cultural History as a guide for the analyses. The source of the research belongs to the collection “Obras Raras Digital Collection”, from the Arthur Vianna Public Library, from the Tancredo Neves Convention Center (CENTUR). From the analysis of photographs, news and chronicles, the female presence in common life sociabilities was evidenced, including walks in squares, entertainment, visits to theaters and participation in sporting events, as spectators, on a larger scale, and as athletes, in minor. At the end of the research, it was concluded that in a Belém influenced by the Brazilian modernist movement, which idealized a new national identity and, in the case of Belém, also Amazonian, the so-called modernity did not apply to women. from the 1920s, an image that referred to the end of the 19th century and the beginning of the 20th century, that is, an image of youth, beauty, grace, modesty, motherhood and good manners, whether in festivities or in sports practices. Although portraying and even constructing the aforementioned ideal, the “Week: Revista Illustrada” was a vehicle for the insertion of the woman from Belen into the world of sociabilities throughout the time frame of the research.